A case report of infantile parkinsonism-dystonia-2 caused by homozygous mutation in the SLC18A2 gene. (4th May 2023) - Zhai, Hongyin; Zheng, Yaofeng; He, Yiduo; Zhang, Yong; Guo, Zhikuan; Cui, Wenzhe; Sun, Li
Abstract: Background: The monoamine neurotransmitter disorders are neurometabolic syndromes caused by disturbances in the synthesis, transport and metabolism of the biogenic amines (the catecholamines dopamine, norepinephrine and epinephrine; serotonin), which are increasingly recognized as an expanding group of inherited neurometabolic syndromes. Case Description: A 6-month-old male infant who presented with developmental delay and suspected cerebral palsy was diagnosed with infantile parkinsonism-dystonia-2 (MIM: 618049). The whole-exome sequencing identified a homozygous c.710C > T (p.Pro237His) transition in the monoamine transporter gene SLC18A2, which was due to paternal uniparental disomy (UPD) of chromosome 10p15.3q26.3, resulting in brain dopamine-serotonin vesicular transport disease. Sanger sequencing confirmed that his unaffected father carried the same mutation in the heterozygous state, while his mother did not carry the same mutation. Autosomal recessive gene mutations in SLC18A2 has been identified in three families in different countries. The infant was treated with pramipexole, a dopamine agonist, and the static tremor was better compared with that before treatment, but the movement disorder was not significantly improved. Conclusion: This case confirmed the causal mutation of SLC18A2 gene and brain dopamine-serotonin vesicular transport disease, which suggested the mechanism of UPD homozygous formation, and confirmed that dopamine agonist treatment could improve some symptoms in affected individuals.